The Relationship of Nurse’s Workload and Caring in Internal Disease Ward and Surgery Ward in Regional Public Hospital - Gilang Ramadhan; Mahfud Mahfud; Zulpahiyana Zulpahiyana (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2018)
Background: Caring is the efforts conducted by nurses to be close with the client to provide appropriate interventions in accordance with the problems experienced. One that causes bad nurses' caring behaviors is their workload that is not balanced. Workload is all activities undertaken by nurses during their duties in a nursing unit. Research Objective: To find out the correlation between workload and nurses' caring behaviors in internal disease ward and surgical ward of Dr. Tjitrowardojo Regional Public Hospital, Purworejo. Research Method: This research was a quantitative research using cross sectional design. The population in this study were all nurses working in Internal Disease Ward and Surgical Ward of Dr. Tjitrowardojo Regional Public Hospital, Purworejo. The total sample was 65 using total sampling technique. The research instruments for workload was using NASA-TLX questionnaire and for nurses' caring behaviors was using a questionnaire. The data processing was using Kendall's tau statistical test. Research Results: The results showed that the majority of respondents with a high workload implemented caring behaviors in the category of enough by 19 respondents (29.2%), while the respondents with very high workload implemented caring behaviors in the category of less by 9 respondents (13.8%). The Kendall's tau analysis showed the results of p = 0.000 (p < 0.05) and r = -0.618, meaning that there was a correlation between workload and nurses' caring behaviors in internal disease ward and surgical ward of Dr. Tjitrowardojo Regional Public Hospital, Purworejo with strong correlation and negative correlation, meaning that the higher the workload, then the lower the caring behaviors. Conclusion: There was a correlation between workload and nurses' caring behaviors in internal disease ward and surgical ward of Dr. Tjitrowardojo Regional Public Hospital, Purworejo